Electromagnetic Noise Optimal Control Technology for Traction Motor ofthe 250 km/h Standard EMU - XU Shaolong; FU Xiangyu; HU Liang; GAN Weiwei; GUO Wei (Kongzhi Yu Xinxi Jishu)
The 250 km/h standard EMU platform is a fully autonomous high-speed EMU platform for different speed levels. Its output is characterized by high frequency and low carrier ratio due to the limitation of the highest switching frequency, which makes the inverter output rich in harmonic components. The problems of motor vibration and electromagnetic noise caused by harmonics are particularly prominent. In this paper, an optimal control strategy for electromagnetic noise of traction motor was proposed. The optimal matching point of the inverter-motor is obtained by reducing the harmonic content of motor current and optimizing the harmonic distribution through flux tracking control technology and switching frequency distribution optimization, so as to reduce motor noise. The experimental results show that the electromagnetic noise optimization control technology can effectively suppress the electromagnetic noise caused by the radial electromagnetic force wave generated by the interaction between harmonic and air gap magnetic field.